Positive and negative impacts of specialty malts on beer foam: a comparison of various cereal products for their foaming properties1. (11th April 2013) - Combe, Alexander L; Ang, Justin K; Bamforth, Charles W
Abstract Background The foam stability of beer is dependent on the presence of foam‐stabilizing polypeptides derived from the cereals from which it is made. It has long been argued that there is a tendency to boost the foam‐stabilizing capabilities of these polypeptides at the heating stages involved in the production of the grist materials. The present study started with the intent to confirm whether these changes occurred and to assess the extent to which different cereal products differed in their foam‐stabilizing tendencies. Results Cereal products differ enormously in their foam‐stabilizing capabilities. Heavily roasted grains, notably black malt and roast barley, do have superior foaming properties. However, certain specialty malts, notably crystal malts, display inferior foam performance. The observed foaming pattern is a balance between their content of foam‐positive and foam‐negative components. Products such as pale malt do contain foam‐negative materials but have a net balance in favour of foam‐stabilizing entities. By contrast, wheat malt and especially black malt have a heavy preponderance of foam‐positive components. Crystal malt displays the converse behaviour: it contains low‐molecular‐weight foam‐negative species. Several of the cereal products appear to contain higher‐molecular‐weight foam inhibitors, but it appears that they are merely species that are of inherently inferior foam‐stabilizing capability to the foaming polypeptides from egg white that were employed to probe the system. The foam‐damaging species derived from crystal malt carried through to beers brewed from them. Conclusion Intense heating in the production of cereal products does lead to enhanced foam performance in extracts of those products. However, not all speciality malts display superior foam performance, through their development of foam‐negative species of lower molecular weight. © 2013 Society of Chemical Industry